The Structural and Preservation Conditions for Shale Gas Enrichment and High Productivity in the Wufeng—Longmaxi Formation, Southeastern Sichuan Basin. Issue 3 (June 2015) - Guo, Tonglou; Zeng, Ping
We have analysed the Wufeng–Longmaxi shale gas field (gas pool) in the Southeastern Sichuan Basin in the light of previous studies on the main constraints of shale gas field enrichment in North America. We have demonstrated that, unlike the relatively simple tectonic evolutionary history of its North American counterparts, South China, represented by the Sichuan Basin and its peripheral areas, has undergone multiple uplifting events and intense folding and thrusting processes. After the distribution of high-quality shale formations has been identified, the structural and preservation conditions are important determinants of the level of shale gas enrichment and productivity. For a complex structural area that has experienced high thermal evolution to become enriched in shale gas and highly productive, the following prerequisites are indispensable: (1) normal structures, i.e. uplifts and anticlines, the latter being the most favourable structural type for shale gas enrichment; (2) hyperpressure, which is not only an important identifier of the presence of a regionally closed environment, but also, an important signature of natural gas pool enrichment; (3) late regional strike-slipping processes and good roof and floor conditions—the existence of structural conditions for forming and maintaining a compressional-shearing environment and a roof and floor that provide good closure are critical indicators of shale gas enrichment in complex structural areas; (4) distance to any regional aqueous layers and avoidance of faults channelling these aqueous layers.